Peranan Kontrasepsi Dahulu, Sekarang dan Masa Depan - Eka Rusdianto Gunardi; Denny Khusen; Kevin Winston (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2018)
Contraceptives play an undeniable important role in woman’s lives. It is widely accepted that the availability of both hormonal and non-hormonal modern contraceptives have improved 0 women’s lives worldwide by allowing women to control their own fertility. Indirectly, contraceptives have been shown to reduce maternal mortality, unwanted pregnancy, and overpopulation. However, the contraceptives available today may not be suitable for all users. Furthermore, there is still need to expand available current contraceptives choices especially long-term contraceptives in order to improve acceptability. As a result, several novel products such as implants, contraceptive vaginal rings, and transdermal patches have recently been introduced in family planning programs. Additional issue of contraceptive needed to be addressed is the adverse effects of hormonal contraceptives. Therefore, new combinations with an improved metabolic profile is currently being researched. Generally, the introduction of new methods with additional health benefits and less side effects would help women with their unmet needs to obtain access to a wider range of contraceptives.